2020
DOI: 10.7717/peerj.10122
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding protein as a novel biomarker for sepsis-related acute kidney injury

Abstract: Background Sepsis-related acute kidney injury (AKI) is associated with high morbidity and mortality among patients. Underlying pathomechanisms include capillary leakage and fluid loss into the interstitial tissue and constant exposure to pathogens results in activation of inflammatory cascades, organ dysfunction and subsequently organ damage. Methods To identify novel factors that trigger sepsis-related acute kidney injury, plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Here we found that septic patients to whom renal replacement therapy had to be administrated had higher serum levels of HBP at admission, whereas in the non-septic patients such a correlation was not found. This is in line with previous research, reporting the highest HBP levels among sepsis patients with AKI undergoing RRT [ 32 ]. A significant association between HBP serum concentration and peak creatinine was found only in the sepsis group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Here we found that septic patients to whom renal replacement therapy had to be administrated had higher serum levels of HBP at admission, whereas in the non-septic patients such a correlation was not found. This is in line with previous research, reporting the highest HBP levels among sepsis patients with AKI undergoing RRT [ 32 ]. A significant association between HBP serum concentration and peak creatinine was found only in the sepsis group.…”
Section: Discussionsupporting
confidence: 93%
“…Pajenda et al . reported significantly higher mean values of HBP among sepsis patients with AKI compared to sepsis patients without AKI [ 32 ]. HBP adds a predictive value to other known risk factors for S-AKI, in 511 sepsis patients of whom 20% developed AKI stage 2–3 within 5 days [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linder et al [48] Infection with organ dysfunction (n = 328) Ma et al [51] Control group (n = 120) Olinder et al [53] Sepsis (n = 100) Pajenda et al [55] Patients without AKI (n = 17) Saridaki et al [56] Severe respiratory failure (SRF) Tian et al [57] Active AOSD (n = 20)…”
Section: Halldorsdottirmentioning
confidence: 99%